The Textiles of Üzüür Gyalan: Towards the identification of a nomadic weaving tradition in the Mongolian Altai - Pearsen, Kristen Rye; Mönkhbayar, Chuluunbat; Enkhbat, Galbadrakh; Bayarsaikhan, Jamsranjav (Archaeological Textiles Review, 2019)
This paper presents the analysis of textiles from the tenth century Mongolian rock burial of Üzüür Gyalan. It is the only undisturbed rock burial discovered to date and presents a unique opportunity to examine a complete set of grave goods, both organic and inorganic, included in a Medieval horse-accompanied burial. The high degree of preservation and the prevalence of woven wool textiles set it apart from other rock burials where silk, sheepskin, and felt garments have been found. Certain features of the assemblage, including the abundance of the woven wools, their technical consistency, and evidence for household rather than specialised production, suggest the work of local weavers. Drawing comparisons with a living nomadic weaving tradition in Ladakh, Tibet, this paper relates aspects of the assemblage to production in a mobile pastoralist context.